qanda-logo
search-icon
Símbolos
Problema
solution-image
a) $3x^{2}+4x^{2}-5x^{2}=$ b) $6x^{3}-2x^{3}+3x^{3}=$ c) x+ 4x- 7x= d) $-2x^{4}+6x^{4}+3x^{4}-5x^{4}=$ e) $7x+9x-8x+x=$ ) 2y + 5y - 3y = 9) $3x^{2}y-6x^{2}y+5x^{2}y=$ h) $4xy^{2}-xy^{2}-7xy^{2}=$ a°= i) $2a^{6}-3a^{6}-2a^{6}+a^{6}$ 6ab-4ab= ) $ab^{3}+3ab^{3}-5ab^{3}+6ab^{3}$ k) $xy^{2}z-2xy^{2}z+xy^{2}z-6xy$ = I) $-x^{3}+5x-2x+3x^{3}+x+2x^{3}$ m) $x^{4}+x^{2}-3x^{2}+2x^{4}-5x^{4}+8x^{2}=$ $-5ab^{2}+a^{2}b+ab^{2}=$ n) 3a'b-5ab+ 73 . p) $12x^{5}-x^{5}-4x^{5}-2x^{5}-3x^{5}=$ q) ) $x^{2}y^{2}-5x^{2}y^{2}-\left(3x^{2}y^{2}-4$ 4x'y') - 8x'y= t) x+x= $\dfrac {1} {2}x^{3}-\dfrac {5} {2}x^{3}+\dfrac {3} {2}x^{3}=$ v) $-\left(ab^{3}+a^{3}b\right)-3a^{3}b+5ab^{3}-\left(a^{3b-2ab^{3}}\right)=$ $7x^{2}-\dfrac {1} {2}x^{2}-\dfrac {5} {2}x^{2}+2x^{2}+\dfrac {3} {2}x^{2}=$ x) $-x+x^{2}+x^{3}+3x^{2}-2x^{3}+2x+3x^{3}=$
Secundaria
Aritmética y álgebra
Búsquedas: 408
Solución
answer-user-profile-image
Profesor de Qanda - Jessica
answer-reply-image
answer-reply-image
answer-reply-image